Identifying accurate methods of assessing blood pressure and health information by lay volunteers in the Philippines: Adapting a Canadian cardiometabolic health program to LMICs - Ricardo Angeles; Floro Dave Arnuco; Fortunato Cristobal; Lisa Dolovich; Janusz Kaczorowski; Dale Guenter; Kasthuri Selvarajah; Fiona Parascandalo; Jessica Gaber; Gina Agarwal (Clinical Epidemiology and Global Health)
Background: Hypertension is a leading cause of mortality worldwide, especially in low- and middle-income countries (LMICs). In Canada, the Cardiovascular Health Awareness Program (CHAP) was proven effective in reducing cardiovascular hospitalizations. The next research will evaluate an adapted version of CHAP in the southern Philippines (Community Health Assessment Program in the Philippines (CHAP-P)). Methods: Prior to full program adaptation, this two-phase study was conducted to evaluate the most appropriate methods locally for 1) assessing blood pressure (BP) readings and 2) collecting CHAP-P participant information. Phase 1 compared the correlation (Pearson's r) of BP readings of three automated BP monitoring devices (WatchBP Office Target, Omron HEM-7130, Microlife 3QA1); manual measurement by a health care professional; and the gold standard (trained observers using a mercury sphygmomanometer). Phase 2 compared three data collection methods (tablet, cell phone, and paper) used by Barangay Health Workers (BHWs), the local volunteers who will implement the intervention. Errors, missed data, and BHW experiences were explored during each phase. Results: Phase 1: the device most highly correlated with the gold standard for systolic BP was the WatchBP Office Target (r = 0.84). For diastolic BP, the WatchBP Office Target produced the same result as the Omron HEM-7130 (r = 0.67). Manual BP measurement showed a very poor correlation (r < 0.60) with the gold standard. Phase 2: BHWs found cell phones and tablets more accurate and easier than paper. They preferred tablets due to the larger screen. Conclusion: The WatchBP Office target and tablet will be used in the next phase of the project.